Numerical simulation of airflow in animal occupied zones in a dairy cattle building. (October 2019) - Bustos-Vanegas, Jaime Daniel; Hempel, Sabrina; Janke, David; Doumbia, Moustapha; Streng, Judith; Amon, Thomas
Abstract : Air flow assessment in animal husbandry is an important issue in the context of welfare and emission. The aim of this study was to implement a porous medium approach for the numerical simulation of air flow in the animal occupied zone (AOZ) of a dairy building. Computational fluid dynamics (CFD) was used to determine the flow resistance properties, where cow geometry was simplified by a six-cylinder geometry. Three different AOZ were identified and parametric studies were performed to determine the pressure drop depending on the air inlet angle. Viscous and inertial loss terms were calculated by non-linear regression and added to the Navier-Stokes equations for each AOZ as a subdomain. Simulations of the air flow in a barn segment containing the three AOZ (standing, resting and resting in double line) indicated that in most configurations, inertial forces dominated and pressure drop was dependent on the air inlet angle. The viscous and inertial loss terms changed depending on the AOZ. The total pressure drop predicted using the porous medium approach taking into account the different AOZs was in good agreement with the results obtained by simulations using the fully resolved, simplified cow bodies. Highlights: Pressure drop in AOZ varies with the air inlet angle and cows position. Inertial force decreases in half when the air flows transversely. Porous medium approach (PMA) can predict the overall pressure drop. The velocity profile estimated by PMA fits after 3 m in front of the AOZ.